2010
DOI: 10.11613/bm.2010.039
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward plagiarism among pharmacy and medical biochemistry students – cross-sectional survey study

Abstract: Introduction: Plagiarism is one of the most frequent and serious forms of misconduct in academic environment. The cross-sectional survey study was done with aim to explore the attitudes toward plagiarism. Materials and methods: First year students of Faculty of Pharmacy and Medical Biochemistry, University of Zagreb, Croatia (N = 146) were anonymously tested using Attitude toward Plagiarism (ATP) questionnaire. The questionnaire is composed of 29 statements on a 5 point Likert scale, (1 -strongly disagree, 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
(60 reference statements)
3
30
1
1
Order By: Relevance
“…These results were supported by Pupovac et al [13] in their study conducted in Croatia for evaluating the medical student's ATP and stated that more than half of the students were agreed that plagiarized paper does no harm to science and self-plagiarism should not be considered harm.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These results were supported by Pupovac et al [13] in their study conducted in Croatia for evaluating the medical student's ATP and stated that more than half of the students were agreed that plagiarized paper does no harm to science and self-plagiarism should not be considered harm.…”
Section: Discussionmentioning
confidence: 62%
“…[12] Additionally, academic misconduct in the scientific nursing researches can seriously harm the people's life and health, so it needs a great accountability. [13] Doing researches and publishing articles is mandatory in academic nursing field for both the faculty members and postgraduate students, since both of them are often under the pressure to publish articles for job promotion, which enforce them to have a certain number of publications in scientific journals. They may attempt to copy and paste from the internet, where a massive amount of data is simply accessible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupovac et al reported that plagiarism was perceived as not very important (63%), harmless (59%), justified under special circumstances (42%), and sometimes necessary by 35% of respondents. [18] A significant correlation of ATP scores was found to be present with a number of publications, no. of presentations and ATR score (P < 0.05) in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Pupovac et al also reported moderate positive attitude and subjective norms toward plagiarism with moderate to high negative attitude (36 ± 7, 26 ± 4, and 32 ± 6, respectively). [18] Gomez et al in a study among dental faculty and postgraduates reported ATP scores in a moderate category which translates into an insufficient level of seriousness and awareness. [19] Shirazi et al reported that majority of respondents confessed that they had plagiarized at least once in their life.…”
Section: Discussionmentioning
confidence: 99%